THE DEVELOPMENT STRATEGY OF SUGAR CANE MANUFACTURE, PT MADUBARU YOGYAKARTA - Khairani, Lathifah; Waluyati, Lestari Rahayu; Suryantini, Any; Sawadogo, Didier (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
The Indonesian sugar industry is one of the plantation industries which is considered a commercial and strategic commodity. However, the national sugar industry has decreased in meeting national sugar needs. This decrease was due to internal problems and external problems in the sugar industry. Sugar Cane Manufacture, PT Madubaru is the only sugarcane-based private company in Yogyakarta. The study aims to identify internal and external factors that influence the development of PT Madubaru and analyze alternative strategies for the development of Sugarcane Manufacture Madukismo Yogyakarta. Sampling technique used is a purposive sampling method with 38 respondents consisting of eight experts and 30 internal company employees. The analytical method used is the Internal Factor Evaluation Matrix (IFE), External Factor Evaluation Matrix (EFE), and SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). The results show that the strategic position of Sugar Cane Manufacture, PT Madubaru development is in quadrant II (two). The strategic position shows that the strategy is directed at efforts to improve the weaknesses (Weaknesses) of PT Madubaru in order to be able to seize opportunities (Opportunities) that exist. The alternative strategy that can be applied in the development of PT Madubaru are increasing cash inflows by opening creditors and outside investors, Raw processing Sugar to reduce the Cost of Production, continuing to work with Bina Sarana Tani to find new varieties to increase sugarcane productivity, expand markets with market penetration, Raw process sugar to optimize plant capacity, process Raw sugar to optimize sugar production and diversify products to increase funds.